Identification of serum metabolic signatures of environmental-leveled phthalate in the Taiwanese child population using NMR-based metabolomics. (1st January 2023) - Lee, Sheng-Han; Du, Zhi-Yi; Tseng, Wei-Chen; Lin, Wan-Yu; Chen, Mei-Huei; Lin, Ching-Chun; Liang, Hao-Jan; Wen, Hui-Ju; Guo, Yue-Leon; Chen, Pau-Chung; Lin, Ching-Yu
Abstract: Phthalates have become important environmental pollutants due to their high exposure frequency in daily life; thus, phthalates are prevalent in humans. Although several epidemiologic surveys have linked phthalates with several adverse health effects in humans, the molecular events underlying phthalate exposure have not been fully elucidated. The purpose of this study was to reveal associations between phthalate exposure and the serum metabolome in Taiwanese children using a metabolomic approach. A total of 256 Taiwanese children (8–10 years old) from two cohorts were enrolled in this study. Twelve urinary phthalate metabolites were analyzed by high-performance liquid chromatography/tandem mass spectrometry, while a nuclear magnetic resonance-based metabolomic approach was used to record serum metabolic profiles. The associations between metabolic profiles and phthalate levels were assessed by partial least squares analysis coupled with multiple linear regression analysis. Our results revealed that unique phthalate exposures, such as mono-isobutyl phthalate, mono-n-butyl phthalate, and mono (2-ethyl-5-oxohexyl) phthalate, were associated with distinct serum metabolite profiles. These phthalate-mediated metabolite changes may be associated with perturbed energy mechanisms, increased oxidative stress, and lipid metabolism. In conclusion, this study suggests that metabolomics is a valid approach to examine the effects of environmental-level phthalate on the serum metabolome. This study also highlighted potentially important phthalates and their possible effects on children. Graphical abstract: Image 1 Highlights: Serum metabolic perturbation was associated with urinary phthalate levels in children. Levels of MEOHP, MnBP, and MiBP were critical to metabolic changes in child serum. The perturbed metabolites may be involved in energy metabolism, oxidative stress, and lipid metabolism. The metabolomic approach is a powerful tool for studying the health impacts of chemicals at an environmental level.